Planning for the Merdeka Belajar Curriculum at the Ar-Riyadh Palembang Islamic Boarding School - Ahmad Zainuri; Yunita; Zahidal Hakim (Borneo Educational Journal (Borju), 2023)
This study examines the curriculum planning set in the Ar-Riyadh Islamic boarding school environment. The purpose of this research was to find out the learning process, identify curriculum development plans, curriculum development processes, and find out the supporting and inhibiting factors in planning the Merdeka Belajar curriculum in the Ar-Riyadh Islamic boarding school environment. The research method used in this research is qualitative research and field research using interview, observation and documentation techniques. Based on the results of the study, it was found that the Ar-Riyadh Islamic boarding school used the local curriculum created by the mudir and planning in the development of the Islamic boarding school curriculum in the form of forming the character of students, increasing hard skills and soft skills, providing learning in accordance with the conditions and needs of students and increasing competence. teachers who influence career development.